Physicochemical, Radiation Shielding, and Anti-Reflective Properties of PCL/PVC Nanocomposites Reinforced With Microwave-Synthesized FeS2 Nanospheres - Pekdemir, Sibel Selcuk; Kuzu, Serpil Yalcin; Yilmaz, Demet; Pekdemir, Mustafa Ersin; Tas, Recep; Kok, Mediha (Wiley, 2025)
In this study, poly epsilon-caprolactone (PCL)/poly vinyl chloride (PVC) blend nanocomposite films reinforced with microwave-assisted synthesized iron pyrite (FeS2) nanospheres were obtained by the solvent casting method. Characterization of the composites was carried out using attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-IR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), x-ray diffraction (XRD), and scanning electron microscopy (SEM). Gamma-ray shielding properties, including mass attenuation coefficients (MAC), mean free path (MFP), half-value layer (HVL), and effective atomic numbers (Zeff), were determined experimentally using a gamma spectrometer equipped with a ULEGe detector. The results indicate that increasing FeS2 content enhances the gamma shielding performance, with PCL/PVC/10% FeS2 exhibiting the highest attenuation capacity. Additionally, fast neutron shielding was evaluated through neutron equivalent dose measurements, confirming the potential of FeS2 to improve neutron absorption. Theoretical calculations of exposure buildup factors (EBF), fast neutron removal cross-section (Sigma R), mass stopping power (MSP), and projected range (PR) were also computed. Furthermore, anti-reflective properties were assessed by determining albedo parameters, revealing that FeS2 effectively reduces gamma-ray reflection by approximately 12.10%. The results suggest that FeS2 doped PCL/PVC composites have significant potential for use in radiation shielding and anti-reflective coatings in various industrial and biomedical applications.
Keywords: blends; composites; films; nanocrystals; nanoparticles; nanowires; poly(vinyl chloride)